Two new polyketides from Hawaiian endophytic fungus Pestalotiopsis sp. FT172. Issue 1 (3rd January 2018) - Li, Chunshun; Sarotti, Ariel M.; Yoshida, Wesley; Cao, Shugeng
Graphical abstract: Highlights: Pestalotiotones A (1 ) and B (2 ) are new polyketides, which have not been reported before. The absolute configuration of the secondary alcohols in pestalotiotones A (1 ) was determined by Mosher reaction. J -based configuration analysis was used to determine the configuration. DP4 NMR calculation was utilized to determine the stereochemistry of the new compounds. The biosynthesis of pestalotiotones A (1 ) and B (2 ) has been proposed. Abstract: Two new polyketides, pestalotiotones A (1 ) and B (2 ) were isolated from the cultured broth of Pestalotiopsis sp. FT172. The structures of compounds1 and2 were determined by analysis of HRMS and NMR spectroscopic data. The absolute configurations of compound1 were assigned by Mosher reaction, J -based configuration analysis, and DP4 NMR calculations. Both compounds were tested against cancer cell lines, pathogenic fungi and bacteria.